Bilateral mirror-like image of cervical synovial cyst in adults - Farid Yudoyono; Deasy Herminawaty; Hendra; Dewi Pratiwi; Nasofi Tri Ramdhani (Neurologico Spinale Medico Chirurgico, 2019)
Cervical synovial cysts (SC), however uncommon, can cause radiculopathy and myelopathy. In this study, we report a case of a cervical synovial cyst presented as myelopathy. A 48-year-old man presented with gait disturbance decreased touch senses and increased sensitivity to pain below the C5 level. Magnetic resonance imaging revealed a 0.3-mm, bilateral mirror-like small cystic lesion in the spinal canal with cord compression at the C5-6 level. We performed a bilateral expansive laminoplasty of C5 using a posterior approach and completely removed the cystic mass. Histological examination of the resected mass revealed fibrous tissue fragments with amorphous materials and granulation tissue compatible with a synovial cyst. The patient’s symptoms resolved within 3 months after surgery. Although cervical SC is often associated with degenerative facet joints, clinicians must be aware that SC may lead to neurological deficits.